Periodontal disease: Repercussions in pregnant woman and newborn health—A cohort study - Figueiredo, Marina Guim Otsuka Padovan [UNESP]; Takita, Stefanie Yaemi [UNESP]; Dourado, Bianca Maria Ramos [UNESP]; de Souza Mendes, Helderjan; Terakado, Erick Olsen; de Carvalho Nunes, Hélio Rubens [UNESP]; da Fonseca, Cátia Regina Branco [UNESP] (Public Library of Science (PLoS), 2019)
The periodontal disease during pregnancy triggers an exacerbated immune response with high local and systemic concentrations of inflammatory markers. Objective To investigate the repercussion of periodontal disease (PD) in the pregnant woman health and the complications during pregnancy and delivery, as well as negative outcomes for the newborn (as infections, prematurity, low birth weight and fetal growth restriction). Method Retrospective cohort study, based on medical records of 142 pregnant women assisted at a prenatal service of usual risk between 2012–2014, with a dental evaluation for PD. Maternal variables, along with labor and newborn variables, were analyzed. The newborns were stratified into two groups: offspring of mothers with PD (subdivided into Severe Periodontal Disease—SPD) and offspring of mothers without PD. Each outcome was adjusted by a multiple logistic regression model, with significance for p-value <0.05, considering all potential confounding factors. Results Among women diagnosed with SPD, the odds ratio for vulvovaginitis was 3.45 times greater (OR = 3.45, p-value = 0.050) and 5.59 times higher for premature rupture of membranes (OR = 5.59; p-value = 0.017). For neonates, the chance of fetal growth restriction was 11.53 times higher for pregnant women with SPD (OR = 11.53, p = 0.041). Conclusion The periodontal disease increased the chance of neonatal and maternal negative outcomes, being the fetal growth restriction, vulvovaginitis and premature rupture of the membrane (PROM) the main results driven by the presence of Severe Periodontal Disease.